Granice prawa do przeszukania osoby i wykorzystania dowodów uzyskanych w ramach tego przeszukania w Kanadyjskiej Karcie Praw i Wolności na przykładzie sprawy R. v. A.M., [2008], 1 S.C.R. 569, 2008 SCC 19 - Wagiel, Michał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
One of the basic human rights is the right to the privacy and personal freedom. Interference with these rights can only be made based on the rule which concerns the terms violating the privacy and personal freedom. That creates the issue of acceptability to perform a search based on the reasonable suspicion, including what happens with evidences obtained by this search. The purpose of this work is demonstration of the reasonable suspicion of involvement in a punishable crime existing in Polish and Canadian Law which allows permitting search and use of obtained in this way evidence. The comparative analysis indicates existance of loopholes, which may be the cause of interpretation problems in the Polish Law, after applying the amendment of the Criminal Conduct, which came into force on July 1, 2015.
Keywords: invasion of privacy; The Polish Constitution; integrity of the person; private interests vs the public interest; The Canadian Charter of Rights and Freedoms